Applicability of 3D laser scanning in precision horticulture - Tamás, J.; Riczu, P.; Nagy, G.; Nagy, A.; Jancsó, T.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2011)
Due to the technological development, remote sensing instruments and methods have become widespread in all segments of life (from precision agriculture through architecture to medicine). Among the innovative development of remote sensing instruments the 3D laser scanner is of outstanding importance. Horticultural applicability of terrestrial laser scanning technique is a new innovation in the precision agriculture. The structure of trees and branches, the canopy extension, the fruit yield, which can help to recognize some biophysical parameters, can be determined. The examination was carried out with Leica ScanStation C10 terrestrial laser scanner in the Study and Regional Research Farm of the University of Debrecen near Pallag. In this article the measuring principle, the parameters and horticulture applicability of the terrestrial laser scanner are presented.